Environment and Philosophy: The Aesthetics and the Natural Environment - Tsekos, Christos A.; Petsiou, Thaleia (Scientific Research, 2018)
In this study, after initially identifying the field of Aesthetics and the concept of Aesthetically Remarkable (Beautiful), we are going to analyze the aesthetic categories, which constitute a basic element of Aesthetics, taking into consideration that these aesthetic categories are of primary importance regarding the evaluation of the so-called Aesthetically Remarkable. Subsequently, after the interpretation of the term “Environment”, we are going to elaborate on a significant change in contemporary Aesthetics that is related to the Aesthetics of the natural environment (not only of Art as before), the similarities and differences of the Beautiful in Art and the Nature and the role of Environmental Policy in protecting the beauty of our natural habitat.
Keywords: Aesthetics; Aesthetically Remarkable; Aesthetic Categories; Beautiful in Art and Nature; Environmental Policy